Ecotoxicological aspects and environmental implications of the use of water and sewage treatment sludges - Souza, A. C.Z. [UNESP]; Santos, J. E. [UNESP]; Marin-Morales, M. A. [UNESP]; Mazzeo, D. E.C. (Springer Nature, 2024)
The addition of various environmental contaminants in water resources has demanded high efficiency from water treatment plants in achieving the expected levels of water potability. Moreover, sewage treatment plants have sought to reduce the organic, inorganic, and microbiological pollutant load of effluents before their disposal into water. However, during these processes, by-products called water treatment sludge and sewage sludge are generated. Water treatment sludge is basically composed of sand, clay, silt, a small amount of organic matter, microorganisms, and metals. While sewage sludge is rich in organic matter, macronutrients and micronutrients, besides pathogenic microorganisms, and toxic contaminants. Studies have demonstrated their high toxicity to different animals and plants. Among the ways to detoxify these residues, biostimulation, bioaugmentation, monitored natural attenuation, and composting stand out. The main reuse of these two residues includes soil conditioners and materials for civil construction. Moreover, water treatment sludge can be used for aluminum and iron recovery, and sewage sludge for biogas and bio-oil production. Thus, in view of the growing production and the real need to propose safety measures for the sustainable management of these wastes, this review intends to reflect on the dangers of their inappropriate disposal on environmental health and to divulge ecotoxicological information on these wastes, as well as the reuse potential of both sludges. An active search was performed on the Google Scholar, Springer, National Center for Biotechnology Information, and Scientific Electronic Library Online platforms, where a literature review was carried out on articles published between 1990 and 2022.
Keywords: Bioremediation; Ecotoxicogenetic assays; Ecotoxicology; Sewage sludge; Solid waste; Waste management; Water treatment sludge